2008
DOI: 10.1111/j.1365-2672.2008.03920.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of specific egg yolk immunoglobulin (IgY) against mastitis-causingStaphylococcus aureus

Abstract: Aims:  To evaluate the in vitro activity of egg yolk immunoglobulin (IgY) against mastitis‐causing Staphylococcus aureus. Methods and Results:  Specific IgY was produced by immunizing hens with formaldehyde‐killed Staph. aureus, using a bacterial strain known to cause mastitis. The IgY, of 94% purity, was obtained from yolks by water dilution, salt precipitations, ultrafiltration and gel filtration. ELISA indicated that the IgY produced was specific to the antigen and five Staph. aureus isolates obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…IgY can thus be an alternative method for providing infection control. Comparing our results with those obtained by Zhen shows that the IgY produced here was effective at lower concentrations (Zhen et al 2008).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…IgY can thus be an alternative method for providing infection control. Comparing our results with those obtained by Zhen shows that the IgY produced here was effective at lower concentrations (Zhen et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…This assay was conducted to investigate whether the anti-S. aureus IgY could inhibit S. aureus growth in liquid medium as described by the method of Zhen with some modifications (Zhen et al 2008). The extracted IgY (titer 6400) was dissolved in TSB at concentrations of 1, 2.5, and 5 µg/ml.…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
“…IgY antibodies developed in chickens, using antigens from S. aureus were tested by several authors. Toxigenic S. aureus strains had their growth abrogated in vitro by native antigens of S. aureus (9, 24, 32). Others described antibodies from serum against native SEC (23) and recombinant SEC (26), but this is the first work to describe development of IgY in ostriches immunized with SEC recombinant protein, and tested against growth of S. aureus strains from different origin.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study demonstrated that IgY has bacterial opsonizing properties that improve bacterial phagocytosis. 26 Thus, the clinical impact of IgY prophylaxis is perhaps attributable to immunomodulatory mechanisms that enhance phagocytic activity and subsequent bacterial clearance in the airways. To further explore the plausible opsonizing capacity of anti-Pseudomonas aeruginosa IgY antibodies, in vitro assays evaluating the activity of phagocytes exposed to various strains of P. aeruginosa were established.…”
Section: Introductionmentioning
confidence: 99%